Oral hygiene knowledge of high-risk Grade One children: an evaluation of two methods of dental health education - Hawkins RJ, Zanetti DL, Main PA, Jokovic A, Dwyer JJM, Otchere DF, Locker D (Blackwell Synergy, 2000)
The effectiveness of two methods of dental health education (DHE) for improving oral hygiene knowledge among high-risk Grade One students was evaluated. Fifty elementary schools in the former City of North York, Canada were assigned to one of two groups. In one group, students received a classroombased DHE lesson which was reinforced by two small-group sessions (n½243). In the other group, students received only a single classroom-based DHE lesson (n½206).